Structure and magnetism of catena-poly[copper(II)-µ-dichloro-L-lysine]hemihydrate. Copper chains with monochloride bridges - Santana, Ricardo C. (2012)
We report the preparation and characterization by elemental analysis, infrared (IR), single crystal X-ray diffraction, magnetic measurements and electron paramagnetic resonance (EPR) of the new compound catena-poly[copper(II)-l-dichloro-L-lysine]hemihydrate, with formula C6H14Cl2CuN2O2-H2O)0.5, here after called [Cu(lys)Cl2]. The compound crystallizes in the space group C2 with copper ions in a square pyramidal coordination, and the structure consists of zigzag chains along the b axis bridged by equatorial- apical chlorine bonds with Cu–Cu distance of 3.5414(4) Å, and a small Cu–Cl–Cu angle of 85.47(6)º. Magnetic susceptibility and isothermal magnetization curves reveals a weak antiferromagnetic interaction 2J =-0.30(2) cm-1 supported by the Cu–Cl–Cu bridge connecting CuII neighbors in the chains. EPR spectra at 34.0 GHz were obtained in powdered samples and in a single crystal with B0 in three orthogonal planes. Assuming an axially symmetric molecular g-matrix, we obtained principal g-values g// = 2.2794(9) and g ? ¼ 2:0489ð3Þ from the crystal g-matrix calculated using the observed angular variation of the EPR line position. The angular variation of the line width, largest along the chain direction, is attributed to dipolar couplings between CuII ions in the lattice. The magnetic and EPR results are discussed in terms of the exchange couplings.